Formation of Oxide Layers with Femtosecond Laser on Steel Surfaces for Color Marking - Juhász, Gergely; Berczeli, Miklós; Weltsch, Zoltán (International Journal of Engineering and Management Sciences, 2020)
With the appearance of ultrashort pulse lasers, the researchers have begun working on various laser marking technology. Atmospheric heating and ablation of a surface induce laser coloration of metal surfaces. However, their application is still problematic today in the industry. With the appearance of femtosecond pulse lasers, a new concept became available for color marking. This concept is based on the formation of laser-induced periodic surface structures (LIPSS) on metal surfaces. The purpose of this article is to summarize the literature of laser color marking with ultrashort pulse lasers.